Leveraging Internet Technologies with DICOM WADO. - Lipton, Paul; Nagy, Paul; Sevinc, Gorkem (Journal of Digital Imaging, 2012)
The digital imaging and communications in medicine (DICOM) 3.0 standard was first officially ratified by the national electrical manufacturers association in 1993. The success of the DICOM open standard cannot be overstated in its ability to enable an explosion of innovation in the best of breed picture archiving and communication systems (PACS) industry. At the heart of the success of allowing interoperability between disparate systems have been three fundamental DICOM operations: C-MOVE, C-FIND, and C-STORE. DICOM C-MOVE oversees the transfer of DICOM Objects between two systems using C-STORE. DICOM C-FIND negotiates the ability to discover DICOM objects on another node. This paper will discuss the efforts within the DICOM standard to adapt this core functionality to Internet standards. These newer DICOM standards look to address the next generation of PACS challenges including highly distributed mobile acquisition systems and viewing platforms.